Realita dan Peran Pendidikan Agama Islam Terhadap Sosial Masyarakat - Cantika Mila Soniya; Soleah Soleah; Ulfi Hasanah; Wachid Nur Fauzi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2020)
Islamic Education plays a very important role in society because it is an education that is a milestone of society. Islamic Education continues to be instilled in students by staying based on its sources namely the Qur'an, hadith, Qiyasi, and Ijma ', which aims to create outputs and generations of noble and educated people who are able to play a role in society in accordance with Al- Qur'an, hadith, qiyas and Ijma 'and balance with the times. The main factors that are very influential will be the birth of a good or bad output depends on 4 factors, namely the curriculum delivered to students, teacher exemplary, family attention to students, and the community environment. Therefore we must prepare these 4 things well so that we are able to create outputs that are moral and highly educated.